Новый метод приготовления глицериновых препаратов - Янковский, А.В. (Вестник зоологии, 1975)
Balsam diffusion from a binding frame may be avoided using glycerine-formol instead of pure formol for constant preparations destined for studies of Protoxoa and small invertebrates, e.g. plankton samples, «in fixo». Squeesing and deformation effects of glycerine disappear entirely after equal distribution of the objects on the slide and their adhesion by ether absolute alcohol-celloidin, with subsequent washing of the slide in diluted alcohol and water.